The global economic crisis : a study of its implications and aftermath. - Bevelin Suprijanto. (2010)
The global financial crisis which originated in the United States of America in 2007 is undoubtedly the biggest economic disaster that the world has seen since the Great Depression of the 1930s. A combination of government policies and flawed financial architecture had laid the foundation to a crisis. The crisis spread from Wall Street to Main Street, and created a domino-effect, crippling financial institutions abroad and throwing economies around the world into disarray. This paper attempts to study the crisis in detail, from its underlying causes to the aftermath. In addition, we hope to draw lessons from this, understand what policies governments can take to prevent a repeat as such, as well as possible challenges that lie ahead for policy makers in the near future.